2023
DOI: 10.1038/s41419-023-05647-w
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the tumor immune microenvironment by cancer-derived circular RNAs

Abstract: Circular RNA (circRNAs) is a covalently closed circular non-coding RNA formed by reverse back-splicing from precursor messenger RNA. It is found widely in eukaryotic cells and can be released to the surrounding environment and captured by other cell types. This, circRNAs serve as connections between different cell types for the mediation of multiple signaling pathways. CircRNAs reshape the tumor microenvironment (TME), a key factor involved in all stages of cancer development, by regulating epithelial-stromal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 121 publications
0
8
0
Order By: Relevance
“…Previous studies have revealed that circRNAs can interact with the tumor immune microenvironment by participating in multiple approaches ( 19 ). In addition to participating in M2 polarization and interacting with macrophages, circRNAs mediate tumor immune surveillance ( 135 , 136 ), regulate immune escape via PD-L1 ( 137 140 ), regulate natural killer cells’ cytotoxicity ( 141 – 143 ), and regulate neutrophils, myeloid-derived suppressor cells, and cancer-associated fibroblast ( 144 ). However, whether circRNA affects ESCC TME through the aforementioned effects, except M2 polarization, has not yet been reported.…”
Section: Circrnas As a Novel Regulator Of Tumor Microenvironment In Esccmentioning
confidence: 99%
“…Previous studies have revealed that circRNAs can interact with the tumor immune microenvironment by participating in multiple approaches ( 19 ). In addition to participating in M2 polarization and interacting with macrophages, circRNAs mediate tumor immune surveillance ( 135 , 136 ), regulate immune escape via PD-L1 ( 137 140 ), regulate natural killer cells’ cytotoxicity ( 141 – 143 ), and regulate neutrophils, myeloid-derived suppressor cells, and cancer-associated fibroblast ( 144 ). However, whether circRNA affects ESCC TME through the aforementioned effects, except M2 polarization, has not yet been reported.…”
Section: Circrnas As a Novel Regulator Of Tumor Microenvironment In Esccmentioning
confidence: 99%
“… 29 These factors can impede the efficacy of immunotherapy. 15 30 Dysregulation of circRNAs promotes immune destruction evasion and reduced immunotherapy efficacy. CircRNAs employ diverse regulatory mechanisms—from sponging miRNAs and proteins to scaffolding proteins and translating peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research elucidates the involvement of PHD finger proteins in the immune response to cancer therapy, shedding light on their impact on treatment effectiveness. For example, interactions between circular RNAs and PHD proteins influence immune responses, impacting the efficacy of immunotherapy ( Guan et al, 2023 ). Although PHD finger proteins are a recent addition to cancer immunotherapy, their capacity to impact cancer development and shape the immune system’s response to treatment warrants further exploration and consideration.…”
Section: Introductionmentioning
confidence: 99%